Redesain penampang kabel wiring APP pelanggan TM untuk perbaikan akurasi pengukuran kWh - Fadjar Kurniadi (Sekolah Tinggi Teknik PLN, 2020)
Abstract Current Transfomer(CT) accuracy for big customers is very important. Constraints Execution of CT accuracy testing on big customers is quite a lot of customers and scattered, and longtime outage duration. Development of electronic kwh Meter for checking on-site CT customers as a solution to these problems. The onsite CT measurement method is carried out by comparing the primary and secondary of the CT by utilizing the current coil on the electronic kWh Meter. This method has several advantages, lower costs, easy procurement, easy and fast operation, so the duration of outages can be minimized. This method is very supportive in the implementation of the Revenue Assurance program. Keywords: English, , 3-5 words ABSTRAK Akurasi CT (Current Transfomer) pada pelanggan besar sangat penting. Kendala Pelaksanaan pengujian akurasi CT pada pelanggan besar adalah pelanggan cukup banyak dan tersebar, dan waktu pemadaman yang lama. Pengembangan kwh Meter Alat untuk pengecekan CT Pelanggan secara on site sebagai solusi permasalahan tersebut. Metode penugukuran CT onsite dilaksanakan dengan membandingkan sisi primer dan sekunder CT dengan memanfaatkan kumparan arus pada kWh Meter elektronik. Metode ini memiliki beberapa keuntungan, antara lain biaya lebih murah, mudah pengadaan,mudah dan cepat dalam pengoperasiannya sehingga lama pemadaman dapat diminimalkan. Cara ini sangat mendukung dalam pelaksanaan program Revenue Assurance dalam memastikan kebenaran CT yang terpasang. Kata kunci: Electronic Meter, CT Testing